Breaking Barriers in Academic Writing: The Uses of Chat AI Models in Empowering International TESOL Students - Gervacio, Marlon Jr (International Journal of Asian Education, 2023)
This study explores Chat AI, specifically Chat Generative Pre-trained Transformer (GPT), among international TESOL students to enhance academic writing. The research addresses the complexity of academic writing for TESOL students and the potential of Chat AI as a promising tool by investigating perceptions, experiences, and impacts. Previous studies note positive outcomes like increased motivation and creativity but also identify limitations, including occasional inaccuracies. Using purposive sampling, this qualitative study involves five international TESOL students with Chat AI experience. Semi-structured interviews, lasting 15-30 minutes, are conducted in person or through video conferencing, recorded, transcribed, and anonymized for thematic analysis. Findings reveal positive perceptions of Chat AI, highlighting convenience, accessibility, and prompt feedback. Despite benefits in idea generation, vocabulary improvement, and template provision, limitations include occasional inaccuracies and plagiarism concerns. Despite drawbacks, Chat AI is seen as valuable for writing proficiency. International TESOL students view Chat AI positively, appreciating its functionalities. Suggestions include incorporating correct references to address plagiarism concerns and establishing responsible usage guidelines. Continued research is recommended for a comprehensive understanding and broader insights from teachers.